(3bhd CHbQGW YfO LGdjfhSs
(3ChdgG (B:s
(3GSeY Hfi hUjI ef fGUM adbO fUMJc , Ef SeYJ , aGbHd GdRfLHjd hGdOGQ adad NPgeG hGdOGQ Ujfi eY bdjd Gdadad s
(3BNQgG (B:s
(3hjchf MO fgGjI GSJYeGdg ai eKbGd HbOQ GdeGcd (B((3cPG(B) (3bOfU HbQGW HgGP cdeg ai MceI LGdjfhS hgh GdCaVd (B((3cPG(B) s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdJGSYs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B183 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs